7, 8-Dihydroxyflavone induces synapse expression of AMPA GluA1 and ameliorates cognitive and spine abnormalities in a mouse model of fragile X syndrome. (February 2015) - Tian, Mi; Zeng, Yan; Hu, Yilan; Yuan, Xiuxue; Liu, Shumin; Li, Jie; Lu, Pan; Sun, Yao; Gao, Lei; Fu, Daan; Li, Yi; Wang, Shasha; et al.
Abstract: Fragile X syndrome (FXS) is characterized by immature dendritic spine architectures and cognitive impairment. 7, 8-Dihydroxyflavone (7, 8-DHF) has recently been identified as a high affinity tropomyosin receptor kinase B (TrkB) agonist. The purpose of this paper was to examine the utility of 7, 8-DHF as an effective pharmacotherapeutic agent that targets dendritic pathology and cognitive impairments in FXS mutant. We synthesized pharmacologic, behavioral, and biochemical approaches to examine the effects of 7, 8-DHF on spatial and fear memory functions, and morphological spine abnormalities in fragile X mental retardation 1 ( Fmr1 ) gene knock-out mice. The study found that 4 weeks of treatment with 7, 8-DHF improved spatial and fear memory, and ameliorated morphological spine abnormalities including the number and elongation of spines in the hippocampus and amygdala. Further mechanism analysis revealed that 7, 8-DHF enhanced the expression of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) GluA1 receptor, but reduced the normal levels of GluA2 at the synapses in Fmr1 . Potentially related to drug-induced changes in AMPA receptor subunits, 7, 8-DHF at the synapses led to phosphorylation of specific serine sites on subunits Ser818 and Ser813 of GluA1, and Ser880 of GluA2, as well as phosphorylation of TrkB, calcium/calmodulin-dependent protein kinase II, and protein kinase C. However, 7, 8-DHF neither affected behavioral performance nor increased TrkB phosphorylation in WT mice, which suggested that it had FXS-specific correcting effect. Altogether, these results demonstrated that 7, 8-DHF improved learning and memory, and reduced abnormalities in spine morphology, thus providing a potential pharmacotherapeutic strategy for FXS. Highlights: 7, 8-DHF improves spatial and fear memory, and ameliorates morphological spine abnormalities in Fmr1 KO mice. 7, 8-DHF enhances the expression of GluA1, but reduces the normal levels of GluA2 at the synapses in Fmr1 . 7, 8-DHF at the synapses leads to increased phosphorylation of GluA1, GluA2, TrkB, CaMKII, and PKC. 7, 8-DHF neither affects behavioral performance nor increases TrkB phosphorylation in WT mice.